A study to determine if estrogen (E) is needed to induce de novo progesterone (P) receptors on gamma/delta t cells as evidenced by determining the degree of rise of progesterone induced blocking factor (PIBF) following P exposure in males - J.H. Check; A. DiAntonio; D.L. Check; M.P. Dougherty; G. Diantonio (Clinical and Experimental Obstetrics & Gynecology, 2020)
Purpose: To determine if exposure to progesterone (P) alone without prior estrogen (E) exposure can cause a rise in serum progesterone induced blocking factor (PIBF). Materials and Methods: Male volunteers received IM progesterone 100 mg for seven days. Baseline and day seven levels of serum P and PIBF were taken. PIBF was measured using a non-commercial newly developed ELISA assay. Results: A significant rise in PIBF was found in male volunteers on day seven. Conclusions: The precipitous rise in serum PIBF in males despite a short exposure to progesterone shows that a person does not need E to induce PIBF secretion by gamma/delta T cells. The possibility still exists pending future studies that E may improve PIBF secretion.